PENERAPAN METODE FORWARD CHAINING DALAM MENDIAGNOSA TANAMAN JATI UNTUK NILAI JUAL EKSPOR - Dedi Suhendro; Eka Irawan (JSR : Jaringan Sistem Informasi Robotik, 2022)
Expert systems are made to transfer the knowledge possessed by experts into a system, so that it is expected to provide answers to a problem. An expert system for diagnosing diseases in teak is an alternative from a variety of expert systems that can be used to overcome the problems encountered. The purpose of designing this expert system is so that users can diagnose diseases in teak plants based on the symptoms entered into the system. The development of this expert system uses a knowledge base that is stored in a database using Paradox, based on rules with forward tracking methods. The results obtained from consultation with this system indicate that the system is able to determine the disease and solutions or suggestions based on the symptoms inputted by the user whose main purpose is for export sales value.